(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2013)
The article under consideration is about the flavoring sensations and the shades of sensation, which arising from reading those works of art, in which in detail tells about the methods of cooking, thus the recipes offer to the reader.